Wernicke’s encephalopathy in pregnancy - Devi R., Auxeelia Packia; Naregal, Basavaraj N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Wernicke’s encephalopathy (WE) is a reversible neurological emergency which is a rare but known complication of hyperemesis gravidarum due to thiamine deficiency. Prolonged vomiting in pregnancy results in thiamine depletion. Most frequently Wernicke’s encephalopathy is found among persons suffering from excessive drinking. Unusually it can also be seen in women presenting with hyperemesis gravidarum with pre-existing malnutrition, as avitaminosis can result from the acute malnutrition associated with prolonged pregnancy-related hyperemesis. The early recognition of its clinical signs and symptoms is essential to establish the suspected diagnosis and can be confirmed by MRI. Most patients present with the triad of ocular signs, ataxia, and confusion. It can be associated with life-threatening complication like central pontine myelinolysis. Here we stress upon the importance of early diagnosis and prompt treatment of WE. The aim of this report is to present cases of Wernicke’s encephalopathy induced by hyperemesis gravidarum except one case which was acute in onset. The course of the disease, clinical signs, diagnostic tools, treatment and its results are presented.